Fintech P2P Lending: The Phenomenon of the Digital Financial Industry, Problems, and an Analysis from the Perspective of Islamic Economic Law - Aulia Azka; Maria Arista Ulfa (Jurnal Hukum Ekonomi Syariah, 2024)
The P2P lending industry in Indonesia has rapidly developed as an alternative financing option for the public, particularly for micro, small, and medium enterprises (MSMEs). This study aims to analyze the phenomenon of fintech P2P lending, including the opportunities it offers and the challenges the industry faces, with an emphasis on the perspective of sharia economic law. However, this growth encounters challenges, including the presence of illegal P2P lending platforms, a lack of public understanding of sharia-compliant financial products, and regulatory hurdles. This research uses a literature review method to collect relevant data and information from various sources, including reports from the Financial Services Authority (OJK) and previous studies. The findings indicate that while fintech P2P lending holds great potential to enhance financial inclusion and support economic growth, strict regulations and public education are crucial to ensuring compliance with sharia principles. Therefore, this study recommends increased cooperation between regulators, industry players, and the public to create a healthy and sustainable fintech ecosystem.